2005
DOI: 10.1088/0022-3727/38/10a/012
|View full text |Cite
|
Sign up to set email alerts
|

Goniometric and topographic characterization of synthetic IIa diamonds

Abstract: Synthetic type IIa diamonds were characterized using rocking curve measurements and x-ray topography with quasi-plane-wave incidence, and high resolution reciprocal space mapping. The rocking curves of the (111) crystals were comparable to the theoretical ones. Some crystals had wider rocking curves because of the higher density of stacking faults. Even the highest quality crystal did not give the theoretical rocking curve due to dislocations and strain bands. On the other hand, the (100) crystals had nearly p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 20 publications
0
18
0
3
Order By: Relevance
“…5 and 6, confirming the excellent crystalline quality (containing few impurities and few dislocations) of the (001) growth sector in the large type IIa diamond crystal. Previous investigation 8) revealed that the RC of the (001) growth sector of the synthetic type IIa crystal grown on the (001)-oriented seed is almost equivalent to the theoretical value. Figure 7 shows UV-excited luminescence images of these crystalline plates captured with DiamondView.…”
Section: Resultsmentioning
confidence: 82%
“…5 and 6, confirming the excellent crystalline quality (containing few impurities and few dislocations) of the (001) growth sector in the large type IIa diamond crystal. Previous investigation 8) revealed that the RC of the (001) growth sector of the synthetic type IIa crystal grown on the (001)-oriented seed is almost equivalent to the theoretical value. Figure 7 shows UV-excited luminescence images of these crystalline plates captured with DiamondView.…”
Section: Resultsmentioning
confidence: 82%
“…The collaboration of SPring-8 with Sumitomo Electric Industries Ltd. (SEI) has successfully developed high-quality synthetic diamond in type IIa. 10 After the performance test at a SPring-8 undulator beamline, we found that a photon flux of a diamond (111) double-crystal monochromator agrees with the theoretical value in the photon energy below 20 keV. 11 However, the beam image is still imperfect.…”
Section: Diamond Crystalmentioning
confidence: 64%
“…The experiment was performed at RIKEN SR physics beamline (BL19LXU) at SPring-8 (Yabashi et al, 2001). We used a high-quality synthetic type IIa diamond (Tamasaku et al, 2005) as a nonlinear crystal. The photon flux of the pump wave was 9:3 Â 10 11 photons s À1 at an energy of E p ¼ 11:0 keV.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the rocking curve in the parametric down-conversion of X-rays into extreme ultraviolet (X ! X + EUV parametric downconversion) was measured with sufficient accuracy, and was found to be asymmetric, while a Lorentzian line shape was predicted theoretically (Tamasaku & Ishikawa, 2007). At present, the underlying mechanism of the asymmetric rocking curve is unknown.…”
Section: Introductionmentioning
confidence: 92%